Behaviour of heavy metals and natural radionuclides in the mixing of phosphogypsum leachates with seawater. (1st January 2021) - Guerrero, J.L.; Pérez-Moreno, S.M.; Gutiérrez-Álvarez, I.; Gázquez, M.J.; Bolívar, J.P.
Abstract: Phosphogypsum (PG) is disposed worldwide in large stacks usually placed in coastal zones, as in the case of Huelva (SW of Spain), where around 100 Mt of PG are stored on the salt marshes of the Tinto River estuary covering a surface of about 1000 ha. This management generates the weathering of PG, and due to its high acidity (pH ≈ 2) and pollutant load can provoke significant emissions into their surroundings. In this work were evaluated by laboratory experiments the effects of pH increase in the behaviour of heavy metals and natural radionuclides during the mixing of phosphogypsum leachates with seawater. The acidic phosphogypsum leachates showed concentrations of heavy metals from two to three orders of magnitude higher than natural continental waters, and natural radionuclides (U-isotopes and 210 Po) from four to five orders of magnitude higher than unperturbed aquatic systems. Major elements and some heavy metals as Mn, Ni, Cd, As, Sb and Co showed a conservative behaviour during the neutralisation of the leachates with seawater, remaining in the liquid phase, while other ones as Al, Fe, Cr, Zn, Cu, Pb precipitated and/or were adsorbed onto the solid phase. The U-isotopes and 210 Po showed a clear non-conservative behaviour probably due to coprecipitation/adsorption processes onto the formed precipitates, but while 210 Po reached a total removal at pH ≈ 7, U- isotopes after a total removal at pH ≈ 5 returned into the liquid phase due to redissolution/desorption processes at near neutral pH. The formed precipitates, mainly composed by iron phosphates particles, showed heavy metal and natural radionuclide concentrations from one to three orders of magnitude higher than unperturbed soils. All these facts demonstrate the serious environmental impact produced by the PG stacks into their surroundings and the urgency of effective restoration measures. Graphical abstract: Image 1 Highlights: Mixing of acidic phosphogypsum leachates with seawater. Effects of pH increase in the behaviour of heavy metals and natural radionuclides. Precipitation and/or adsorption onto the solid phase of Al, Fe, Cr, Zn, Cu, Pb. Coprecipitation/adsorption of U-isotopes and 210 Po. Highly polluted precipitates by heavy metals and natural radionuclides. Abstract : Findings: The main finding is the evaluation of heavy metals and natural radionuclides behaviour during the mixing of PG leachates with seawater and the environmental impact due to the enrichment of these pollutants in the particulate phase.